EARLY ASSESSMENT OF THE RISK OF DYSLEXIA AND DYSGRAPHIA AMONG CHILDREN AGED 5-6 IN THE ASPECT OF EDUCATIONAL AND THERAPEUTIC WORK OF KINDERGARTENS - Klim-Klimaszewska, Anna; Nazaruk, Stanislawa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Reading and writing are basic skills that guarantee child’s learning. Therefore, it is important that the child has mastered these skills to the best extent. Unfortunately, not all children can meet the requirements in the field of learning to read and write. Problems of varying intensity and range appear, they are caused by various disorders of the perceptual-motor functions. Children who may have problems with reading and writing in the future can already be seen in the kindergarten. Therefore, the aim of the study was to diagnose the risk of dyslexia and dysgraphia among children aged 5-6. The study included 300 children from kindergartens in Biała Podlaska, Poland. The results of the study showed that children at risk for dyslexia and dysgraphia are present in the study group. The most frequent manifestations of these disorders were in the field of fine motor skills, gross motor skills, language functions, visual functions and attention. They were caused by various factors related to the functioning of the nervous system that affect its development. Among the children diagnosed with these disorders, therapeutic measures have been taken to help reduce developmental delays and make it easier for them to learn in primary school.